Experiences with and perspectives on advance care planning in young- and late- onset dementia: A focus group study with physicians from various disciplines - Van Rickstal, Romy; De Vleminck, Aline; Engelborghs, Sebastiaan; Van den Block, Lieve (Frontiers in Aging Neuroscience, 2023)
Introduction Despite the relevance of advance care planning (ACP) for people with dementia, its uptake in this population is particularly low. Several challenges for ACP in dementia have been identified from physicians’ perspectives. However, the literature available mainly includes general practitioners and focuses exclusively on the context of late-onset dementia. This is the first study to inquire physicians from four highly relevant specialisms in dementia care, with a focus toward potential specificities based on patients’ age. The research question of this study is: “What are physicians’ experiences with and perspectives on discussing ACP with people with young- and/or late-onset dementia?”. Methods Five online focus groups were conducted with 21 physicians (general practitioners, psychiatrists, neurologists and geriatricians) in Flanders, Belgium. Verbatim transcripts were analyzed through the qualitative method of constant comparative analysis. Results Physicians believed that the societal stigma related to dementia influences people’s reaction to their diagnosis, at times characterized by catastrophic expectations for the future. In this regard, they explained that the topic of euthanasia is sometimes addressed by patients very early in the disease trajectory. Respondents paid ample attention to actual end-of-life decisions, including DNR directives, when discussing ACP in dementia. Physicians felt responsible for providing accurate information on both dementia as a condition, and the legal framework of end-of-life decisions. Most participants felt that patients’ and caregivers’ wish for ACP was more driven by who their personality than by their age. Nonetheless, physicians identified specificities for a younger dementia population in terms of ACP: they believed that ACP covered more domains of life than for older persons. A high consistency regarding the viewpoints of physicians from differing specialisms was noted. Discussion Physicians acknowledge the added value of ACP for people with dementia and especially their caregivers. However, they face several challenges for engaging in the process. Attending to specific needs in young-onset, in comparison to late-onset dementia, requires ACP to entail more than solely medical domains. However, a medicalized view on ACP still appears to be dominant in practice as opposed to its broader conceptualization in academia.